Kalinin: an epithelium-specific basement membrane adhesion molecule that is a component of anchoring filaments (The Rockefeller University Press, 1991)
Basal keratinocytes attach to the underlying dermal stroma through an ultrastructurally unique and complex basement membrane zone. Electron- dense plaques along the basal surface plasma membrane, termed hemidesmosomes, appear to attach directly to the lamina densa of the basement membrane through fine strands, called anchoring filaments. The lamina densa is secured to the stroma through a complex of type VII collagen containing anchoring fibrils and anchoring plaques. We have identified what we believe is a novel antigen unique to this tissue region. The mAbs to this antigen localize to the anchoring filaments, just below the basal-dense plate of the hemidesmosomes. In cell culture, the antigen is deposited upon the culture substate by growing and migrating human keratinocytes. Addition of mAb to the cultures causes the cells to round and detach, but does not impair them metabolically. Skin fragments incubated with antibody extensively de- epithelialize. These findings strongly suggest that this antigen is intimately involved in attachment of keratinocytes to the basement membrane. This antigen was isolated from keratinocyte cultures by immunoaffinity chromatography. Two molecules are observed. The most intact species contains three nonidentical chains, 165, 155, and 140 kD linked by interchain disulfide bonds. The second and more abundant species contains the 165- and 140-kD chains, but the 155-kD chain has been proteolytically cleaved to 105 kD. Likewise, two rotary-shadowed images are observed. The larger of the two, presumably corresponding to the most intact form, appears as an asymmetric 107-nm-long rod, with a single globule at one end and two smaller globules at the other. The more abundant species, presumably the proteolytically cleaved form, lacks the distal small globule. We propose the name "kalinin" for this new molecule.